Perceived support and AI literacy: the mediating role of psychological needs satisfaction - Shen, Yanyan; Cui, Wencheng (Frontiers in Psychology, 2024)
The advent of Artificial Intelligence (AI) has had a profound influence on both our professional and personal spheres. College students must possess a fundamental understanding of AI to navigate and adapt effectively to our constantly evolving society. However, the factors influencing college students' AI literacy within the emerging field of AI education (AIEd) remain unclear. According to self-determination theory (SDT), the extent to which students' psychological needs are satisfied may impact their AI literacy. This study aimed to examine how the satisfaction of students' psychological needs mediates the relationship between two types of support (technical and teacher) and AI literacy. A cross-sectional survey involving 445 university students from diverse academic backgrounds was conducted for this purpose. The study revealed that although both types of support positively influenced the fulfillment of the three psychological needs, only the fulfillment of autonomy and competence needs served as predictors and mediators in the relationship between the two types of support and AI literacy. Satisfaction of relatedness needs did not act as a mediator. Contrary to expectations, the two forms of support were not directly linked to students' AI literacy. It is recommended that teachers provide support for AIEd to address the psychological needs of students. Furthermore, schools should offer specialized courses in AI literacy to students.